2006 IEEE International Conference on Acoustics Speed and Signal Processing Proceedings
DOI: 10.1109/icassp.2006.1660220
|View full text |Cite
|
Sign up to set email alerts
|

A Decoder for Lvcsr Based on Fixed-Point Arithmetic

Abstract: The increasing computational power of embedded CPU's motivates the fixed-point implementation of highly accurate largevocabulary continuous-speech (LVCSR) algorithms, to achieve the same performance on the device as on the server. We report on methods for the fixed-point implementation of the frame-synchronous beam-search Viterbi decoder, N-grams language models, and HMM likelihood computation. This fixedpoint recognizer is as accurate as our best floating-point recognizer in several LVCSR experiments on the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This strict implementation of the mixture of Gaussian models is complex as it involves highly nonlinear operations. However, it has been shown that by taking the maximum of all of the mixtures instead of the sum, a very good approximation of the result could be obtained [10]. Hence, by taking the negative of the logarithm of equation (1) in order to convert probabilities into costs and applying the previous approximation, the acoustic cost can be evaluated by:…”
Section: A Gaussian Calculationmentioning
confidence: 98%
“…This strict implementation of the mixture of Gaussian models is complex as it involves highly nonlinear operations. However, it has been shown that by taking the maximum of all of the mixtures instead of the sum, a very good approximation of the result could be obtained [10]. Hence, by taking the negative of the logarithm of equation (1) in order to convert probabilities into costs and applying the previous approximation, the acoustic cost can be evaluated by:…”
Section: A Gaussian Calculationmentioning
confidence: 98%
“…This strict implementation of the mixture of Gaussian models is complex as it involves highly nonlinear operations. However, it has been proven that taking the maximum of all of the mixtures, instead of the sum, is a very good approximation of the result [17]. Hence, by taking the negative of the logarithm of (1) in order to convert probabilities into costs and applying the previous approximation, the acoustic cost can be evaluated by where α is a coefficient per mixture that encompasses all constants and parameters outside of the exponential function in (1).…”
Section: Gaussian Calculationmentioning
confidence: 99%